Islet Biology and Metabolism - Kebede, Melkam; Yau, Belinda (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue of Metabolites, entitled "Islet Biology and Metabolism" is dedicated to islet research and the impact of islet function in metabolic health and disease. Specific topics include, but are not limited to, islet hormone processing and secretion, islet transplant research, novel proteins of the insulin secretory pathway, as well as islet drug targets for the management of T1D and T2D.